THE EFFECT OF AI-DRIVEN PERSONALIZED MARKETING ON CONSUMER PURCHASE DECISIONS: EVIDENCE FROM THE FASHION INDUSTRY - Suleman, Dede; Wianti, Wiwin; Sofyanty, Devy; Ariawan, Joko; Dwi Setyaningrum, Etik (PT. Media Edutama Nusantara, 2025)
This study explores the impact of AI-driven personalized marketing on consumer behavior in the fashion industry, focusing on purchase decisions and intentions. Using a quantitative approach, data from 350 respondents were analyzed to examine direct, mediated, and moderated relationships among key variables. The results reveal that AI-driven personalized marketing significantly influences consumer purchase decisions and intentions, highlighting its effectiveness in aligning with consumer preferences. Message relevance and brand loyalty are confirmed as mediators, demonstrating their critical roles in enhancing the impact of personalization strategies. Additionally, consumer trust in AI moderates the relationship between AI-driven marketing and purchase decisions, amplifying its effect when trust levels are high. These findings contribute to the theoretical understanding of personalized marketing by integrating mediating and moderating variables, offering a nuanced perspective on consumer engagement. Practically, the study emphasizes the importance of building trust, delivering relevant messages, and fostering loyalty to optimize marketing strategies in the fashion industry. The research provides actionable insights for businesses aiming to leverage AI-driven personalization to drive both short-term sales and long-term consumer engagement in a competitive digital marketplace.